Modification of NiO-based transporting materials for featuring highly efficient photovoltaic - Siow, Hwa Teo; Shuzi Hayase; Tingli Ma (Faculty of Science & Natural Resources, UMS, 2024)
The performance of high-efficiency inverted perovskite solar cells (PSCs) heavily depends on the quality of the hole transporting layer (HTL) and its interfaces. This study explores how incorporating lanthanum (La) into the NiOx matrix affects defect passivation, ultimately enhancing charge extraction capabilities and stability without sacrificing power conversion efficiency. The introduction of La results in a noticeable improvement in the quality of the La–NiOx layer, eliminating the formation of pinholes. Furthermore, La incorporation modifies the energy band alignment, which enhances hole transport and increases the open-circuit voltage (Voc) beyond 1 V compared to pure NiOx. The advantageous impact of La is further confirmed through photoluminescence measurements, demonstrating effective passivation of trap states. Significantly, PSCs utilizing La–NiOx as the HTL exhibit a 21% increase in efficiency and superior stability compared to those with pristine NiOx. Remarkably, solar cells doped with 3 moles% La maintained 95% of their efficiency after 50 days of storage in a moisture-free desiccator, and 98% efficiency retention was observed for cells stored in a glovebox, substantially outperforming pristine counterparts. The positive effects of La incorporation also extend to the conductivity of the solar cells, evidenced by a reduction in charge transfer resistance (Rct) from 3100 Ω in pristine cells to 1200 Ω. Additionally, the presence of La shortens the carrier lifetime, indicating reduced recombination processes and more efficient charge carrier transfer from the perovskite layer. Overall, while there is still room for enhancing the power conversion efficiency of La–NiOx PSCs through further modifications, the addition of La has demonstrably improved their stability, paving the way for future commercialization opportunities.